Hunters in the dark eaudiobook - Osborne, Lawrence (Recorded Books Inc., 2016)
From the novelist the New York Times compares to Paul Bowles, Evelyn Waugh and Ian McEwan, an evocative new work of literary suspense Adrift in Cambodia, Robert Grieve - pushing thirty and eager to side-step a life of quiet desperation as a small-town teacher - decides to go AWOL. As he crosses the border from Thailand, he tests the threshold of a new future. And on that first night, a small windfall precipitates a chain of events involving a bag of "jinxed" money, a suave American, a trunk full of heroin, a hustler taxi driver, a corrupt policeman, and a rich doctor's daughter, in which Robert's life is changed forever. Hunters in the Dark is a sophisticated game of cat and mouse, where identities are blurred, greed trumps kindness, and karma is ruthless. Filled with Hitchcockian twists and turns, suffused with the steamy heat and pervasive superstition of the Cambodian jungle, and unafraid to confront uneasy questions about luck and the machinations of fate, this is a masterful novel that has the feel of an instant classic.